2019
DOI: 10.1186/s13000-019-0817-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutation profiles of follicular thyroid tumors by targeted sequencing

Abstract: Background One of the major challenges remaining in the classification of thyroid tumor is the determination of whether a nodule is benign or malignant. We aimed to characterize the mutational profiles of follicular thyroid tumor and to identify markers with potential diagnostic and prognostic implications. Methods Targeted sequencing with a panel of 18 thyroid cancer-related genes was performed on 48 tissue samples from follicular thyroid adenoma (FTA), 32 follicular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 35 publications
0
47
0
1
Order By: Relevance
“…The similarity of the somatic mutation profiles among FAs and FTCs supports the point raised regarding FTCs more likely being a continuum of FAs rather than a distinct diagnostic entity and will probably add to the ongoing scientific discussion (20,21). Recent studies have explored the possible correlation of the somatic mutation signature and burden to histopathological diagnostic classes and found no substantial correlation (2,15,22,23). However, two of the studies succeeded in showing a significant correlation between patient prognosis and mutational signature and/or overall mutation load (15,23).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The similarity of the somatic mutation profiles among FAs and FTCs supports the point raised regarding FTCs more likely being a continuum of FAs rather than a distinct diagnostic entity and will probably add to the ongoing scientific discussion (20,21). Recent studies have explored the possible correlation of the somatic mutation signature and burden to histopathological diagnostic classes and found no substantial correlation (2,15,22,23). However, two of the studies succeeded in showing a significant correlation between patient prognosis and mutational signature and/or overall mutation load (15,23).…”
Section: Discussionmentioning
confidence: 55%
“…Recent studies have explored the possible correlation of the somatic mutation signature and burden to histopathological diagnostic classes and found no substantial correlation (2,15,22,23). However, two of the studies succeeded in showing a significant correlation between patient prognosis and mutational signature and/or overall mutation load (15,23). In brief, the study by Nicolson et al (15) correlated the somatic signature of 39 FTC to both diagnosis and prognosis and found that mutation burden was associated to a worse prognosis, independent of histopathological classification.…”
Section: Discussionmentioning
confidence: 99%
“… 7 The histopathological interpretation of capsular or vascular invasion varies and depends on the discretion of pathologists which leads to imprecise classification. 5 This led to calls that classification based on discretion should be discouraged to allow for careful and adequate clinical classification. 8 …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Recently, published literature increasingly suggested that somatic mutations in BRAF, HRAS, KRAS, NRAS, TERT, RET, PIK3CA, PTEN, TP53, CTNNB1,AKT1, GNAS, PAX8/PPARγ, NTRK1, and TSHR genes have been associated with diagnosis and treatment of TC. [7][8][9][10][11][12][13][14][15][16] Next generation sequencing (NGS) is a newlydeveloped technique offered a cost-effective approach for detecting multiple genetic alterations and provided quantitative assessment of mutation frequency. 17,18 Therefore, a panel designed to these 15 target genes was used to detect molecular alterations by NGS in PTC.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, single gene assays, such as BRAF V600E mutation, have been commonly used for finding molecular alterations by Sanger sequence, immunohistochemistry, and real time PCR in PTC 5,6 . Recently, published literature increasingly suggested that somatic mutations in BRAF, HRAS, KRAS, NRAS, TERT, RET, PIK3CA, PTEN, TP53, CTNNB1,AKT1, GNAS, PAX8/PPARγ, NTRK1, and TSHR genes have been associated with diagnosis and treatment of TC 7‐16 . Next generation sequencing (NGS) is a newly‐developed technique offered a cost‐effective approach for detecting multiple genetic alterations and provided quantitative assessment of mutation frequency 17,18 .…”
Section: Introductionmentioning
confidence: 99%